2008
DOI: 10.1128/aem.01395-08
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Extraintestinal Pathogenic Escherichia coli Strains from Human and Avian Sources Reveals a Mixed Subset Representing Potential Zoonotic Pathogens

Abstract: Since extraintestinal pathogenic Escherichia coli (ExPEC) strains from human and avian hosts encounter similar challenges in establishing infection in extraintestinal locations, they may share similar contents of virulence genes and capacities to cause disease. In the present study, 1,074 ExPEC isolates were classified by phylogenetic group and possession of 67 other traits, including virulence-associated genes and plasmid replicon types. These ExPEC isolates included 452 avian pathogenic E. coli strains from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
276
2
15

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(311 citation statements)
references
References 45 publications
18
276
2
15
Order By: Relevance
“…This particular plasmid replicon type has previously been associated with virulence in poultry (Johnson et al, 2007(Johnson et al, , 2008, and horizontal transfer of plasmids of this replicon type might represent a risk factor for changing a commensal E. coli into a more virulent form (Cusumano et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This particular plasmid replicon type has previously been associated with virulence in poultry (Johnson et al, 2007(Johnson et al, , 2008, and horizontal transfer of plasmids of this replicon type might represent a risk factor for changing a commensal E. coli into a more virulent form (Cusumano et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when Moulin-Schouler et al (33) compared O18:K1 ExPEC strains of human and avian origin for common virulence factors and genetic relationship, they found that APEC and NMEC share several virulence factors and overlap in their phylogenetic grouping. Also, in a study of over 1,000 ExPEC from human and avian sources, Johnson et al (24) found a mixed cluster of ExPEC subpathotypes (APEC, NMEC, and UPEC) that shared much overlap in their virulence genotypes and belonged to serogroups, MLST types, and phylogenetic groups that typify human pathogens. They regarded the isolates of this mixed cluster as being potential zoonotic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…E-mail: lknolan@iastate.edu AVIAN DISEASES 56:192-199, 2012 Key words: APEC, colibacillosis, ExPEC, immunization, Iss, vaccine Abbreviations: APEC 5 avian pathogenic Escherichia coli; ELISA 5 enzyme-linked immunosorbant assay; ExPEC 5 extraintestinal pathogenic E. coli; GST 5 glutathione-S-transferase; GST-Iss 5 glutathione-S-transferase-Iss (the fusion protein); HICS 5 hyperimmune chicken sera; IPTG 5 isopropyl-b-D-thiogalactopyranoside; NMEC 5 neonatal meningitis E. coli; PBS 5 phosphate-buffered saline; PBSt 5 phosphate-buffered saline with 0.05% TweenH 20; SPF 5 specific-pathogen-free; UPEC 5 uropathogenic E. coli Avian pathogenic Escherichia coli (APEC), the causative agent of colibacillosis, is a major problem for the poultry industry in the United States, resulting in significant losses annually (3). Additionally, recent reports, providing evidence of a link between APECcontaminated poultry (21) and extraintestinal pathogenic E. coli (ExPEC)-caused neonatal meningitis (24,44) and urinary tract infections in human beings (24,39), suggest that control of avian colibacillosis may have a beneficial impact on both avian and human health. Control of colibacillosis is problematic, with the increased restrictions on the use of antimicrobial agents in poultry making vaccine-based control, where appropriate, increasingly desirable.…”
mentioning
confidence: 99%
“…Detection, definition and determination of distribution of molecular pathotypes of APEC in poultry farms of every province of Iran, in different hosts, could be considered as a potential approach to control colibacillosis in the country (Johnson et al 2008). Our preliminary work used this objective in our study area to find the prevalent molecular pathotype in border region of Iran.…”
Section: Discussionmentioning
confidence: 99%